2023
DOI: 10.1021/acs.joc.3c01474
|View full text |Cite
|
Sign up to set email alerts
|

A Fries-Type Rearrangement Strategy for the Construction of Stereodefined Quaternary Pseudoanomeric Centers: An Entry into C-Naphthyl Ketosides

Haijuan Liu,
Mylène Lang,
Damien Hazelard
et al.

Abstract: The stereodefined construction of quaternary pseudoanomeric centers by way of a BF 3 •Et 2 O-catalyzed, Fries-type rearrangement of O-ketosides is described. This method provides new access to C-naphthyl ketosides related to biologically relevant products with good to complete stereocontrol in favor of the β product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The use of a highly polar solvent mixture (nitromethane/chloroform) almost totally abolished the formation of the cyclized products 7 (entry 12). As observed in our previous work (Scheme 1), 12 lower yields were observed when the phenol in 1a was unprotected (see the Supporting Information, Scheme SI-2). At this stage, control experiments from pure compounds 7a and 7b were conducted to assess if the observed stereoselectivity of the cyclization reaction was due to a thermodynamically driven equilibration (see the Supporting Information, Scheme SI-6).…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The use of a highly polar solvent mixture (nitromethane/chloroform) almost totally abolished the formation of the cyclized products 7 (entry 12). As observed in our previous work (Scheme 1), 12 lower yields were observed when the phenol in 1a was unprotected (see the Supporting Information, Scheme SI-2). At this stage, control experiments from pure compounds 7a and 7b were conducted to assess if the observed stereoselectivity of the cyclization reaction was due to a thermodynamically driven equilibration (see the Supporting Information, Scheme SI-6).…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…Finally, we examined several 1,5-bis-glycopyranoside substrates bearing a substituted phenyl group instead of the 4-methoxy-naphthalenyl motif (Scheme b). In a previous related study (Scheme ), we indeed found that the nature of the aromatic aglycone moiety strongly influenced the outcome of the Fries-type rearrangement, the substrate scope being limited so far to O -naphthyl ketosides. This result could be attributed in part to the higher reactivity of naphthalenes compared to the corresponding benzene derivatives in electrophilic substitution reactions .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations